Assessment of Bisphenol A (BPA) Exposure in Dairy Cows Using Hair Samples Analysis - Slawomir Gonkowski; Manolis Tzatzarakis; Nariste Kadyralieva; Elena Vakonaki; Thomas Lamprakis; Ismail Sen; Askarbek Tulobaev; Fatih R. Istanbullugil; Aidai Zhunushova; Liliana Rytel (Animals)
Bisphenol A (BPA) is a plasticizer known to have various adverse effects on humans and animals. Exposure of farm animals to BPA negatively impacts their health and poses a threat to humans who consume products of animal origin. Despite the importance of studying the exposure of farm animals to BPA, the knowledge in this area is quite limited. To date, the assessment of BPA levels in dairy cows using analysis of hair samples has not been performed. The study utilized liquid chromatography-mass spectrometry to analyze hair samples collected from 48 dairy cows in the following regions of Kyrgyzstan: Sokuluk, Alamedin and Ysyk Ata. BPA levels above the limit of detection (LOD = 4.8 pg/mg) were noted in 18.8% of analyzed samples. BPA levels in individual samples ranged from below LOD to 89.1 pg/mg with a median value of 9.3 ± 19.7 pg/mg. The study indicates that dairy cows are exposed to BPA, and hair samples can be used for BPA biomonitoring in farm animals. The present study is the first investigation of BPA levels in cows’ hair, which is one of the best matrices to study long-term exposure of living organisms to environmental pollutants. Additionally, this study is the first to analyze BPA in biological samples from Kyrgyzstan.